Investigating the Targeting Power to Brain Tissues of Intranasal Rasagiline Mesylate-Loaded Transferosomal In Situ Gel for Efficient Treatment of Parkinson's Disease - Hala N. ElShagea; Rana R. Makar; Alaa H. Salama; Nermeen A. Elkasabgy; Emad B. Basalious (MDPI AG, 2023)
Rasagiline mesylate (RSM) is a hydrophilic drug with poor oral bioavailability (36%) because of hepatic first-pass metabolism. The present study focuses on delivering RSM directly to the brain through its inclusion within transferosomal in situ gel administered through the intranasal (IN) route. Transferosomes were formed by the thin-film hydration method with the aid of Design-Expert® software by varying the edge activator (EA) type in the absence or presence of cholesterol. By desirability calculations, the optimum formulation was composed of phosphatidylcholine and sodium deoxycholate as an EA (5:1% w/w) with no cholesterol. The optimum formulation was 198.63 ± 34.98 nm in size and displayed an entrapment efficiency of 95.73 ± 0.09%. Transmission electron microscopy revealed discrete and spherical vesicles. Optimized transferosomes were further incorporated into an in situ gel composed of 0.5% pectin, 15% Pluronic® F-127, and 5% Pluronic® F-68 and tested for the in vivo performance. The systemic as well as brain kinetics were assessed in rats by comparing the IN-administered in situ gel to the IV aqueous solution. The optimum in situ gel showed safety and biocompatibility on rats' nasal mucosa with enhanced brain bioavailability (131.17%). Drug targeting efficiency and direct transport percentage indices (304.53% and 67.16%, respectively) supported successful brain targeting offering direct nose-to-brain drug delivery.